2014
DOI: 10.1016/j.physa.2014.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Identifying influential spreaders by weighted LeaderRank

Abstract: Identifying influential spreaders is crucial for understanding and controlling spreading processes on social networks. Via assigning degree-dependent weights onto links associated with the ground node, we proposed a variant to a recent ranking algorithm named LeaderRank [L. Lü et al., PLoS ONE 6 (2011) e21202]. According to the simulations on the standard SIR model, the weighted LeaderRank performs better than LeaderRank in three aspects: (i) the ability to find out more influential spreaders, (ii) the higher … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
144
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(145 citation statements)
references
References 37 publications
(42 reference statements)
1
144
0
Order By: Relevance
“…Martin et al [30] made the point that the eigenvector centrality has lost the capacity to distinguish among the remaining nodes and introduced an alternative centrality definition called nonbacktracking centrality. The LeaderRank algorithm was modified by introducing a variant based on allocating degree-dependent weights onto associations constructed by ground nodes [31]. Zhao et al [32] identified the most effective spreaders by using community-based theory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Martin et al [30] made the point that the eigenvector centrality has lost the capacity to distinguish among the remaining nodes and introduced an alternative centrality definition called nonbacktracking centrality. The LeaderRank algorithm was modified by introducing a variant based on allocating degree-dependent weights onto associations constructed by ground nodes [31]. Zhao et al [32] identified the most effective spreaders by using community-based theory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the link relationship between webpages can be explained as the correlation and support between webpages, so too can the importance of the webpage be judged. Typical methods include the Hypertext-Induced Topic Search (HITS) algorithm [25] proposed by Kleinberg, the PageRank algorithm [26] used by Google and LeaderRank [27] proposed recently by Lv Linyuan et al Then in 2014, Weighted LeaderRank [28] as an improvement method was presented by Li et al Current research on identifying influential spreaders, many interesting conclusions were successively put forward, such as the role of clustering [29] by Chen D-B et al who also proposed to improve the identification of influential spreaders by the path diversity [30].…”
Section: Introductionmentioning
confidence: 99%
“…As consequence eigenvector, centrality may lead to improper ranking if applied to such networks. Various studies have used PageRank and its extensions to identify the influential spreaders in OSNs [22][23][24][25][26][27]. Kitsak et al found, in contrast to common belief, there are plausible circumstances where the best spreaders do not correspond to the most highly connected or the most central people [28].…”
Section: Related Workmentioning
confidence: 99%
“…The most prominent ones include classical centrality measures in complex networks such as degree centrality [40][41][42], betweenness centrality [43], closeness centrality [44], and eigenvector centrality [45][46][47] , PageRank [22][23][24]48] and it extensions and k-core algorithm [28,49,50] . Classical centrality measurements rely on network topology.…”
Section: Influential Spreaders Identification Algorithms In Complex Nmentioning
confidence: 99%